Mesenchymal Stromal Cells and Their Secretome: New Therapeutic Perspectives for Skeletal Muscle Regeneration - Sandonà, Martina; Di Pietro, Lorena; Esposito, Federica; Ventura, Alessia; Silini, Antonietta Rosa; Parolini, Ornella; Saccone, Valentina (Frontiers in Bioengineering and Biotechnology, 2021)
Mesenchymal stromal cells (MSC) are multipotent cells found in different tissues: bone marrow, peripheral blood, adipose tissue, skeletal muscle, perinatal tissues and dental pulp. MSC are able to self renew and to differentiate into multiple lineages, and they have been extensively used for cell therapy mostly owing to their anti-fibrotic and immune-regulatory properties that have been suggested to be at the basis for their regenerative capability. MSC exert their effects by releasing a variety of biologically active molecules such as growth factors, chemokines, and cytokines, either as soluble proteins or enclosed in extracellular vesicles (EV). Analysis of MSC-derived secretome and in particular studies on EV are attracting great attention from a medical point of view due to their ability to mimic all the therapeutic effects produced by the MSC (i.e. endogenous tissue repair, regulation of the immune system). MSC-EV could be advantageous compared to the parental cells because of their specific cargo containing mRNAs, miRNAs and proteins that can be biologically transferred to recipient cells. MSC-EV storage, transfer and production are easier and their administration is also safer than MSC therapy. The skeletal muscle is a very adaptative tissue, but its regenerative potential is altered during acute and chronic conditions. Recent works demonstrate that both MSC and their secretome are able to help myofiber regeneration enhancing myogenesis and interestingly, can be manipulated as a novel strategy for therapeutic interventions in muscular diseases like muscular dystrophies or atrophy. In particular, MSC-EV represent promising candidates for cell free-based muscle regeneration. In this review, we aim to give a complete picture of the therapeutic properties and advantages of MSC and their products (MSC-derived EV and secreted factors) relevant for skeletal muscle regeneration in main muscular diseases.